Utilization of the index of efficiency for estimating the influence of seed vigor on growth and seedling development - Navarro, Marlen; Febles, Gustavo; Torres, Verena (Cuban Journal of Agricultural Science, 2017)
For utilizing the index of efficiency as integration measurement and estimative element for determining the influence of seed vigor on initial growth and development of the seedlings, a completely randomized design with factorial arrangement (6 x 13) was applied, determined by the scarification methods (sulphuric acid, hot water, soaking 24 h, cover cut, puncture and the control) and storage times (0, 1, 2, 3, 4, 5, 6, 7, 8,9, 10, 11 and 12 months from starting the storage). According to the methodology, 30 days after sowing the variable seedling height, length of the root system length of the hypocotyl , fresh weight of the root system and fresh weight of the aerial part were evaluated in the nursery. In the six experimental treatments, seedling height outstood as one the variables of highest preponderance in MC1. The matrices of efficiency showed that 4 mday is the evaluation in which the variables of greater preponderance are expressed in the five scarification methods, while for the control was 0 mday. Pre-sowing treatments included in the soaking method with water at environmental temperature and cover cut, reflected the best represented in the groups of high vigor, with 69.2 and 53.8 % from the total of storage times assessed. The index of efficiency allowed estimating that seeds evaluated at 4 mday propitiate the best growth and development of the seedlings, without disregarding the influence of the evaluations at 2 and 3 mday on seed vigor in 50 % of the pre-sowing methods, even the control. Key words: vigor, Albizia, index of efficiency, scarification